AMPK does not play a requisite role in regulation of PPARGC1A gene expression via the alternative promoter in endurance-trained human skeletal muscle - Popov, D. V.; Lysenko, E. A.; Butkov, A. D.; Vepkhvadze, T. F.; Perfilov, D. V.; Vinogradova, O. L. (Experimental Physiology, 2017)
In human skeletal muscle, PGC-1a is constitutively expressed via the canonical promoter. In contrast, the expression of PGC-1a mRNA via the alternative promoter was found to be highly dependent on the intensity of exercise and to contribute largely to the postexercise increase of total PGC-1a mRNA. This study investigated the role of AMPK in regulating PGC-1a gene expression via the alternative promoter through a cAMP response element-binding protein-1-dependent mechanism in human skeletal muscle. AMPK activation and PGC-1a gene expression were assayed in skeletal muscle of nine endurance-trained men before and after low-intensity exercise (38% of maximal oxygen uptake) and with or without administration of a single dose (2 g) of the AMPK activator metformin. Low-intensity exercise markedly and significantly increased (~100-fold, P < 0.05) the expression of PGC-1a mRNA via the alternative promoter, without increasing ACCSer79/222 (a marker of AMPK activation) and AMPKThr172 phosphorylation. Moreover, in contrast to placebo, metformin increased the level of ACCSer79/222 phosphorylation immediately after exercise (2.6-fold, P < 0.05). However postexercise expression of PGC-1a gene via the alternative promoter was not affected. This study was unable to confirm that AMPK plays a role in regulating PGC-1a gene expression via the alternative promoter in endurance-trained human skeletal muscle.